Values of Religious Moderation in Islamic Religious Education Learning - Ibrahim, Brian Indra; Obaid, Moh Yahya; Marlina, Marlina (IAIN KENDARI, 2025)
This study seeks to ascertain the principles of religious moderation in the instruction of Islamic religious education at SMP Negeri 4 Kendari. This study employs a descriptive qualitative research methodology, using a field research approach whereby the researcher personally goes and observes the research location to gather data and information via observation, interviews, and documentation approaches. The data was analysed following the methodology of Miles, Huberman, and Saldana, which involves three steps: data condensation, data display, and conclusion drawing or verification, subsequently analysed through data reduction, presentation, and conclusion formulation. The data verification method employs technological triangulation and source triangulation. The research findings indicate that the incorporation of religious moderation values in PAI instruction at SMP Negeri 4 Kendari involves planning by PAI educators following their orientation on religious moderation from the Indonesian Ministry of Religion. Subsequently, these valuesare implemented in PAI education, particularly benefiting students, as evidenced by their ability to demonstrate mutual respect, appreciation for local culture, opposition to radicalism, and tolerance towards non-Muslim peers. Initiatives to assist educators in promoting the principles of religious moderation within PAI instruction at SMP Negeri 4 Kendari encompass institutional support through school programs and activities that embody these values. This includes the practice of morning worship prior to educational activities, singing the national anthem